Collagen‐Derived Porous Carbons: Porous Carbons Derived from Collagen‐Enriched Biomass: Tailored Design, Synthesis, and Application in Electrochemical Energy Storage and Conversion (Adv. Funct. Mater. 46/2019). (12th November 2019) - Niu, Jin; Shao, Rong; Liu, Mengyue; Zan, Yongxi; Dou, Meiling; Liu, Jingjun; Zhang, Zhengping; Huang, Yaqin; Wang, Feng
Abstract : Collagen‐enriched biomass materials are promising precursors for low‐cost and advanced functional porous carbons. In article number 1905095, Zhengping Zhang, Yaqin Huang, Feng Wang, and co‐workers review the design and synthesis of collagen‐derived porous carbons, and discuss their specific applications in electrochemical energy storage and conversion systems.